The sentence is "Everybody doesn't get a flushot" and the readings I've come up with are:
A: ∀x∃y((PERSON(x)&FLUSHOT(Y))&~GET(x,y), which is supposed to read out "For every person, x, there is a flushot, y, and not every person got a flushot.
B: ∃y∀x((PERSON(x)&FLUSHOT(Y))->~GET(x,y), which should read "There is a flu shot, y, for every person, x, and if x is a person it did not get y.
Or something like that. I'm incredibly confused by this for some reason and would reallllly appreciate some help, if you have any to offer. Thanks!